Implementation of Android-Based Learning Media on Student Learning Outcomes in SMA Negeri 1 Maros - Malikus, Andi (Institute of Computer Science (IOCS), 2023)
Implementation of android-based learning media on student learning outcomes at SMA Negeri 1 Maros. Thesis of Educational Technology Study Program, Faculty of Teacher Training and Education, University of Muhammadiyah Makassar, guided by Hj. Muliati Samad and H.Abd. Hamid Mattone. The purpose of this study was to determine the implementation of android-based learning media on student learning outcomes at SMA Negeri 1 Maros. The research method used is descriptive quantitative. Respondents were 49 students at SMA Negeri 1 Maros. Data analysis techniques are carried out by calculating the percentage per variable and statistical tests. Based on the results of the study, the authors provide an interpretation of the data on the produt moment correlation index number, through interpretation in a simple way or roughly on rxy. Based on the hypothesis testing, it turns out that the value of thit (0.9280) is greater than ttab (which is only 0.2816). It turns out that the correlation number between variables X and Y is not negative, meaning that between the two variables there is positive correlation, which means the alternative hypothesis (Ha) is accepted. Based on the results of the research above, it can be concluded that the implementation of android-based learning media on student learning outcomes at SMA Negeri 1 Maros has a significant effect.